We have to solve the equation: Int[(sin x)^2 dx]+Int[(cos x)^2 dx] = (x^3-4x)/(x-2)

Now Int [ a dx ] + Int [ b dx] = Int [ (a + b) dx]

Int[(sin x)^2 dx]+Int[(cos x)^2 dx] = (x^3 - 4x)/(x-2)

=> Int [ (sin x)^2 + (cos x)^2 dx] = (x^3 - 4x)/(x-2)

Use (sinx)^2 + (cos x)^2 = 1

=> Int [ 1 dx] = (x^3 - 4x)/(x-2)

=> x = (x^3 - 4x)/(x-2)

=> x = x(x^2 - 4)/(x-2)

=> x - 2 = x^2 - 4

=> x^2 - x - 2 = 0

=> x^2 - 2x + x - 2 = 0

=> x(x - 2) + 1(x - 2) = 0

=> (x + 1)(x - 2) = 0

=> x = -1 and x = 2

But x = 2 makes the left hand side undefined, so we do not consider it.

**The required solution of the equation is x = -1.**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.